2019
DOI: 10.1007/s12035-019-1493-6
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Induced Activation of DNA Damage Responses Drives Senescence-Like State in Postmitotic Cochlear Cells: Implication for Hearing Preservation

Abstract: In our aging society, age-related hearing loss (ARHL) has become a major socioeconomic issue. Reactive oxygen species (ROS) may be one of the main causal factors of age-related cochlear cell degeneration. We examined whether ROS-induced DNA damage response drives cochlear cell senescence and contributes to ARHL from the cellular up to the system level. Our results revealed that sublethal concentrations of hydrogen peroxide (H 2 O 2 ) exposure initiated a DNA damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 65 publications
5
65
0
Order By: Relevance
“…Consistent with these findings, our recent results revealed that sub-lethal concentrations of hydrogen peroxide (H 2 O 2 )-exposure initiated a DNA damage response together with increased levels of key hallmarks of senescent cells, including increased expression levels of p21, and positive senescence-associated β-galactosidase labeling cells in cochlear explants in culture, together with increased inflammatory markers such as p38 and p-p38. Furthermore, high amounts of DNA damage and senescence-like features were observed in the cochlear tissues of SAMP8 mice during aging and were correlated with the accelerated ARHL observed in SAMP8 mice [70]. In addition, an accumulation of age pigment or lipofuscin was observed in the cytoplasm of spiral ganglion neurons of SAMP8 mice [59].…”
Section: Senescence-like Phenotypementioning
confidence: 78%
See 3 more Smart Citations
“…Consistent with these findings, our recent results revealed that sub-lethal concentrations of hydrogen peroxide (H 2 O 2 )-exposure initiated a DNA damage response together with increased levels of key hallmarks of senescent cells, including increased expression levels of p21, and positive senescence-associated β-galactosidase labeling cells in cochlear explants in culture, together with increased inflammatory markers such as p38 and p-p38. Furthermore, high amounts of DNA damage and senescence-like features were observed in the cochlear tissues of SAMP8 mice during aging and were correlated with the accelerated ARHL observed in SAMP8 mice [70]. In addition, an accumulation of age pigment or lipofuscin was observed in the cytoplasm of spiral ganglion neurons of SAMP8 mice [59].…”
Section: Senescence-like Phenotypementioning
confidence: 78%
“…These displayed mitochondrial morphology damage, reduced mitochondrial membrane potentials, an imbalance of mitochondrial fusion/fission, and an impaired mitochondrial respiratory capacity [69]. Furthermore, using an H 2 O 2 exposed cochlear explant in culture and adult SAMP8 mice in vivo, we demonstrated that ROS-induced DNA damage responses drive cochlear cell senescence and contribute to accelerated ARHL [70].…”
Section: Dna Damage and Dna Damage Responsesmentioning
confidence: 83%
See 2 more Smart Citations
“…Senescence-associated b-galactosidase (SA-b-Gal) activity staining The cultured CBM senescence assay was performed by staining for SA-b-Gal activity, and the pH of the SA-b-Gal staining solution was 6, following the manufacturer's instructions and the steps outlined in previous reports (Benkafadar et al 2019;Zhao et al 2013). Briefly, the cell culture medium was removed and the CBM washed once with phosphate-buffered saline (PBS).…”
Section: Cbm Primary Culture and Senescence Model Induced By D-galmentioning
confidence: 99%